Chapter 10: Counter-Terrorism and International Law Since 9/11, Including in the EU-US Context. (2nd February 2015) - De Kerchove, Gilles; Höhn, Christiane
Abstract: The article by EU Counter-Terrorism Coordinator Gilles de Kerchove and his adviser Christiane Höhn provides an inside view into the EU's practices and views related to counter-terrorism and international law. It explains the EU's criminal justice approach to the fight against terrorism and provides arguments for the effectiveness of this response in practice. The authors set out the tools for regional law enforcement and judicial cooperation the EU has adopted since 9/11, based on the principle of mutual recognition, as well as EU-US cooperation in this area. It also looks at the role of the military in the fight against terrorism. In a second part, the article deals with questions related to the international legal framework for the fight against terrorism, such as the existence of not of an armed conflict in the legal sense against Al Qaeda. It also explains relevant initiatives in the EU-US context, including the EU-US legal advisers' dialogue, the EU framework to support the closure of Guantánamo and the EU input to the implementing provisions of the National Defense Authorization Act.